A Colposcopic Evaluation of VIA Positive Cases in a District Hospital of Chittagong Hill Tract, its Pattern and Association with CIN & Ca cervix. (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Background: Cervical cancer remains a significant public health challenge, particularly in low-resource settings. Despite the high burden of cervical intraepithelial neoplasia (CIN) and invasive cancer in Bangladesh, data on disparities between tribal and non-tribal populations in the Chittagong Hill Tract (CHT) region remain scarce.Objective: This study aimed to compare the patterns and associated factors of CIN and invasive cervical carcinoma among tribal and non-tribal VIA-positive women undergoing colposcopy evaluation.Methods: A cross-sectional study was conducted at Bandarban district hospital in CHT, including 284 VIA-positive women. Colposcopic evaluation with guided biopsy was performed, and histopathological findings were categorized as normal, CIN1, CIN2, CIN3, or invasive carcinoma. Sociodemographic and reproductive factors were analyzed for associations.Results: Non-tribal women exhibited higher educational attainment but married earlier and delivered their first child at younger age compared to tribal women (p